AKAL BERTINGKAT DALAM PERSPEKTIF IBNU SINA, ALQURAN, DAN NEUROSAINS SERTA RELEVANSINYA DENGAN PENDIDIKAN ISLAM - Ebit Sutrisna; Suyadi Suyadi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2022)
This research is motivated by the multilevel intellect proposed by Ibn Sina and the tendency of Islamic education in heart management so that it pays less attention to reason education. Some people think that the mind is not in the brain but the soul. This research is included in library research, with a qualitative approach. The results showed that Ibn Sina divided the mind into four levels (1) Al-'Aql al-hayulani; (2) Al-'Aql bi Al-Malakah; (3) Al-'Aql bi Al-Fi'l; and (4) Al-'Aql Al-Mustafad. Furthermore, the Qur'an mentions the basic word of mind ('aql) in the form of fi'il with a total of 49 mentions, one of which uses the past form and 48 others use the present form. This shows that Islam really cares about the role of reason in human life, both as a leader on earth and as a servant of Allah. Based on neuroscience, the location responsible for reasoning is in the brain, which is divided in parts and performs different functions. The relevance to Islamic education is that it should be able to take advantage of all the potential that exists in students, namely in the form of mind, heart, and body, so that students can develop their potential without sacrificing one of them. The research concludes that human reason must be used as much as possible to innovate and create new things that lead to happiness in this world and the hereafter.